Survival Analysis After Neoadjuvant Chemotherapy With Trastuzumab or Lapatinib in Patients With Human Epidermal Growth Factor Receptor 2-Positive Breast Cancer in the GeparQuinto (G5) Study (GBG 44) - Untch, Michael; Von Minckwitz, Gunter; Gerber, Bernd; Schem, Christian; Rezai, Mahdi; Fasching, Peter; Tesch, Hans; Eggemann, Holm; Hanusch, Claus; Huober, Jens; Solbach, Christine; Jackisch, Christian; et al. (Journal of Clinical Oncology, 2018)
Purpose The GeparQuinto phase III trial demonstrated a lower pathologic complete response (pCR; pT0 ypN0) rate when lapatinib was added to standard anthracycline-taxane chemotherapy compared with trastuzumab in patients with human epidermal growth factor receptor 2 (HER2) -positive breast cancer. Here, we report the long-term outcomes. Methods Patients with HER2-positive tumors (n = 615) received neoadjuvant treatment with epirubicin (E) plus cyclophosphamide (C), followed by docetaxel (T) in combination with either lapatinib (L) or trastuzumab (H; ECH-TH arm: n = 307; ECL-TL arm: n = 308). All patients received adjuvant trastuzumab for a total of 12 months and 18 months in the ECH-TH and ECL-TL arms, respectively. Median follow-up was 55 months. Results Three-year disease-free survival (DFS), distant DFS (DDFS), and overall survival (OS) were not significantly different between the two treatment arms. Long-term outcomes correlated with pCR (DFS: hazard ratio [HR], 0.63; P = .042; DDFS: HR, 0.55; P = .021; and OS: HR, 0.31; P = .004). A benefit only for OS was observed in patients who were treated with trastuzumab and achieved pCR versus no pCR (HR, 0.15; P = .010), whereas no difference was found in patients with pCR versus without pCR in the lapatinib arm. DFS and DDFS remained unchanged in both treatment arms according to hormone receptor status, whereas OS was significantly better in hormone receptor-positive patients who were treated with neoadjuvant lapatinib (HR, 0.32; P = .019), followed by adjuvant trastuzumab. No difference was observed in hormone receptor-negative patients; however, the small number of events limits this interpretation. Within the hormone receptor-negative cohort, pCR was significantly associated with DFS, DDFS, and OS ( P = .002, .005, and .002, respectively). Conclusion pCR correlated with long-term outcome. In patients with hormone receptor-positive tumors, prolonged anti-HER2 treatment-neoadjuvant lapatinib for 6 months, followed by adjuvant trastuzumab for 12 months-significantly improved survival compared with anti-HER2 treatment with trastuzumab alone.
EVALuna2:56157